UV cross-linking/immunoprecipitation assay glucocorticoid receptor-adrenergic receptor gene sequence interaction - Bai, Ying (BioTechniques, 2003)
The rat beta 1-adrenergic receptor (beta 1-AR) gene contains glucocorticoid response element (GRE) half-sites at positions -2767 and -945. In electrophoretic mobility shift assay (EMSA) experiments, neither beta 1-AR GRE half-site recognized glucocorticoid receptors (GRs) obtained from baculovirus high-level expression systems or from mammalian cells. We have developed a sensitive UV cross-linking/immunoprecipitation assay, using a 524-bp fragment containing the prototypical GRE obtained from the rat tyrosine aminotransferase promoter sequence and using antibodies recognizing mammalian GR. Using this assay, we provide evidence that rat beta 1-AR gene sequences recognize mammalian GRs expressed in mouse 3T3 cells and that the site of GR interaction does not appear to specifically contain the beta 1-AR GRE half-sites. This represents one of the first reports demonstrating the utility of a UV cross-linking/immunoprecipitation assay in the detection of mammalian GR interaction with beta 1-AR sequences, is consistent with the lack of specific DNA-GR protein complexes observed in EMSA experiments using oligonucleotide probes containing the beta 1-AR GRE half-sites, and provides evidence that mammalian GR interaction occurs at complex rate beta 1-AR gene sequences